The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1038/s41467-018-06310-1
|View full text |Cite
|
Sign up to set email alerts
|

The MinDE system is a generic spatial cue for membrane protein distribution in vitro

Abstract: The E. coli MinCDE system has become a paradigmatic reaction–diffusion system in biology. The membrane-bound ATPase MinD and ATPase-activating protein MinE oscillate between the cell poles followed by MinC, thus positioning the main division protein FtsZ at midcell. Here we report that these energy-consuming MinDE oscillations may play a role beyond constraining MinC/FtsZ localization. Using an in vitro reconstitution assay, we show that MinDE self-organization can spatially regulate a variety of functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 69 publications
(126 reference statements)
5
83
2
Order By: Relevance
“…Each measurement and background was averaged, and statistical outliers were eliminated. Statistical outliers were defined based on the maximum signal for each scan that was less than the first quartile (Q1) or greater than the third quartile (Q3) ( 18 ). Five scans were taken, and discarded reads were not replaced.…”
Section: Methodsmentioning
confidence: 99%
“…Each measurement and background was averaged, and statistical outliers were eliminated. Statistical outliers were defined based on the maximum signal for each scan that was less than the first quartile (Q1) or greater than the third quartile (Q3) ( 18 ). Five scans were taken, and discarded reads were not replaced.…”
Section: Methodsmentioning
confidence: 99%
“…This gradient was capable of localizing FtsZ-YFP-MTS filaments to the middle of the compartment [61]. Very recently, our lab has shown that—even in the absence of MinC—MinD and MinE can support the anticorrelated movement and oscillation of model membrane proteins, including mCherry fused to various membrane targeting sequences, lipid-anchored streptavidin and FtsZ-YFP-MTS [88]. Moreover, if the proteins are permanently anchored to the membrane, MinDE oscillations can localize them to the middle of a microcompartment [88].…”
Section: Synthetic Cell Division Via Reconstitution Of E Coli Divisomentioning
confidence: 99%
“…Very recently, our lab has shown that—even in the absence of MinC—MinD and MinE can support the anticorrelated movement and oscillation of model membrane proteins, including mCherry fused to various membrane targeting sequences, lipid-anchored streptavidin and FtsZ-YFP-MTS [88]. Moreover, if the proteins are permanently anchored to the membrane, MinDE oscillations can localize them to the middle of a microcompartment [88]. This implies that MinD and MinE are sufficient to generate a generic cue for the localization of membrane proteins, which may also be relevant for simplified divisome localization machineries.…”
Section: Synthetic Cell Division Via Reconstitution Of E Coli Divisomentioning
confidence: 99%
“…[65] Membrane bound MinD-ATP recruits MinC with a subsequent inhibitory effect on FtsZ-ring assembly. [67] In further experiments, an adapted cDICE method was used to transfer purified MinD and MinE into giant unilamellar vesicles (GUVs). [62] It could be demonstrated that the MinDE reaction and diffusion system can determine the localization of membrane attached molecules in a spatiotemporal manner without specific molecular interactions in vitro.…”
Section: Spatial Positioning Of the Divisome: Finding Mid-cellmentioning
confidence: 99%